1998
DOI: 10.1016/s0305-0483(97)00078-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic layout algorithms: a state-of-the-art survey

Abstract: It has been over a decade since Rosenblatt published his seminal paper on modelling the dynamic facility layout problem (DFLP). Since then, there have been improvements to Rosenblatt s original dynamic programming model. Alternate solution methods have also been proposed. However, no comprehensive review of the research in the DFLP has been undertaken. In this paper we categorize the different works of research that have followed and discuss them. They include improved and more flexible solution methods, fath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 32 publications
0
50
0
1
Order By: Relevance
“…Recently, Kulturel- Konak and Konak (2015) used SA heuristic to solve unequal area cyclic facility layout problems, but it is not based on FBS. The research works (Kusiak & Heragu, 1987;Balakrishnan & Cheng, 1998;Singh & Sharma, 2006;Drira, et al, 2007;Moslemipour et al, 2012) give the detailed review of various types of facility layout problems and different heuristic and meta-heuristic approaches followed to solve the FLPs. To the best of our knowledge, no research work has observed in the literature, the application of SA algorithm to solve UA-DFLP with FBS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Kulturel- Konak and Konak (2015) used SA heuristic to solve unequal area cyclic facility layout problems, but it is not based on FBS. The research works (Kusiak & Heragu, 1987;Balakrishnan & Cheng, 1998;Singh & Sharma, 2006;Drira, et al, 2007;Moslemipour et al, 2012) give the detailed review of various types of facility layout problems and different heuristic and meta-heuristic approaches followed to solve the FLPs. To the best of our knowledge, no research work has observed in the literature, the application of SA algorithm to solve UA-DFLP with FBS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous papers on this topic have been surveyed in [6], [48] and [54], among others. In this section, we focus on papers that are pertinent to design of layouts in dynamic environments.…”
Section: Literature Review and Classificationmentioning
confidence: 99%
“…A limitation of this approach is that the relative positions of departments are fixed over all the planning periods -only the sizes and shapes are allowed to vary. For a more complete review of papers on the dynamic layout problem, we refer the reader to [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, other changes in the business environment like change in demand pattern cannot be handled simultaneously by the use of these two concepts. In terms of changes in demand pattern, two approaches related to layout design have been developed, including the dynamic layout (Rosenblatt and HAU, 1987;Balakrishnan et al, 1992;Balakrishnan and Cheng, 1998;Kochhar and Heragu, 1999) and robust layout (Rosenblatt and Kropp, 1992;Benjaafar et al, 2002). These approaches aim to add built-in flexibility or robustness to system layout in response to forecasted changes in demand pattern.…”
Section: Introductionmentioning
confidence: 99%